Students’ Error in Solving Percentage Word Problems: An Analysis by Using Newman’s Procedure - Paudel, Krishna Chandra; Ghimire, Shree Prasad (Community College Research Journal, 2025)
Students frequently struggle while in solving the problem in the percentage, beside the common use of percentages in educational and daily lives. The descriptive analysis of the randomly selected answer-sheets of taken from the four students of grade IX. The errors in solving a verbal problem on percentage calculation. In the analysis of the solution given by the students’ shows that many students demonstrated the transformation errors in misunderstandings regarding the percentage and its relationships in understanding of arithmetic aptitudes. Students perceived the concept of percentage increase in additive and then multiplicative processes. Highlighting the errors occur when calculating original values from the increased amount. In this research paper, researcher examines the understanding of students’ problems related to percentage through the lenses of Newman's Error Analysis (NEA) framework. This research paper contributes in enhancing mathematics education by exploring the conceptual challenges in resolving percentage problems. It also recommend the effective instructional approach has explicitly addressed for the ontological transition from additive to multiplicative reasoning. Further this research address the cognitive effect in the mind of students that contradicts existing mental models and focused in restructuring the precise conceptual frameworks.